Hidden potential ebook The science of achieving greater things. - Grant, Adam (2023)
#1 New York Times Bestseller “This brilliant book will shatter your assumptions about what it takes to improve and succeed. I wish I could go back in time and gift it to my younger self. It would’ve helped me find a more joyful path to progress.” —Serena Williams, 23-time Grand Slam singles tennis champion The #1 New York Times bestselling author of Think Again illuminates how we can elevate ourselves and others to unexpected heights. We live in a world that’s obsessed with talent. We celebrate gifted students in school, natural athletes in sports, and child prodigies in music. But admiring people who start out with innate advantages leads us to overlook the distance we ourselves can travel. We underestimate the range of skills that we can learn and how good we can become. We can all improve at improving. And when opportunity doesn’t knock, there are ways to build a door. Hidden Potential offers a new framework for raising aspirations and exceeding expectations. Adam Grant weaves together groundbreaking evidence, surprising insights, and vivid storytelling that takes us from the classroom to the boardroom, the playground to the Olympics, and underground to outer space. He shows that progress depends less on how hard you work than how well you learn. Growth is not about the genius you possess—it’s about the character you develop. Grant explores how to build the character skills and motivational structures to realize our own potential, and how to design systems that create opportunities for those who have been underrated and overlooked. Many writers have chronicled the habits of superstars who accomplish great things. This book reveals how anyone can rise to achieve greater things. The true measure of your potential is not the height of the peak you’ve reached, but how far you’ve climbed to get there.